THE EFFECTS OF SELF-REGULATED LEARNING STRATEGIES ON PRESCHOOL CHILDRENâ€™S SELF-EFFICACY AND PERFORMANCE IN EARLY WRITING - Kim, Siew Siew; Nor, Mariani Md. (UPI Press, 2019)
To enhance the will and the skills to express thoughts explicitly and effectively in early writing among preschool children, self-regulated learning (SRL) was suggested for preschool children as one of the effective learning approaches. This quasi-experimental study involved seventy-five preschool children (5-6 years old) from two public preschools in Selangor, Malaysia. This study investigated the effects of SRL strategies on early writing self-efficacy and early writing performance among preschool children. Interview data was engaged and supported the quantitative result to obtain a deep insight of the findings. Two-way Repeated Measure ANCOVA was employed and confirmed the effectiveness of self-regulated learning intervention with an interaction effect between the test and group for early writing self-efficacy being statistically significant (F(1, 72) = 12.665; p = 0.001, ï¨2= 0.150), with Cohenâ€™s d = 0.84;Â and early writing performance statistically significant (F(1, 72) = 110.801; p 0.001, ï¨2= 0.606), with Cohenâ€™s d = 2.84. The result also confirmed that self-monitoring and controlling (F (5, 69) = 17.934, p 0.001), with an adjusted RÂ² = 0.534, was a strong predictor for early writing self-efficacy, and planning and goal setting (F(5, 69) = 12.706, p 0.001), with an adjusted RÂ² = 0.442, were a strong predictor for early writing performance. Eleven self-regulated learning strategies used emerged from the interviewsâ€™ data pertaining to different contexts. According to the participant children, planning and goal setting, self-monitoring, and self-evaluation were the strategies that will assure their writing quality. These responses supported the results produced by the quantitative data. The findings of this research provide a useful insight into early writing and self-regulated learning instructions in the Malaysian preschool context.